O diário de uma travesti/artista - a busca pela raiz do ódio e memórias performáticas - Silva, Marina Silvério da (2020)
This Master's dissertation speaks about the exchanges and interpersonal relations of the artist / transvestite Marina Silvério with society and how these experiences are expressed through art and the narrative of memories, on the subject Transgender. A diary-shaped memorial recounts some stories that connect Theater and Art (music) with Marina's gender transition, according to her individual point of view, experiences and culture. Confirmation and validation of what is reported in the dissertation occurs through direct and indirect citations in the text, written only by trans people: Dodi Leal, Sayonara Nogueira, Jaqueline Gomes de Jesus, Viviane Vergueiro, Amara Moira, Renata Carvalho, Jota Mombaça and Pêdra Costa. Information on femaleconstruction, the construction of a new US, information and reports on the hormonal treatment of transgender / transvestite women and how society reacts and deals daily when confronted with a transvestite is transmitted. A study is done that seeks possibleorigins and causes of hatred and non-acceptance of trans / transvestites by society. The study takes place through research and interviews with trans and transvestite people and aims to clarify the reasons and possible causes of violence against trans /transvestites, structural transphobia and why society reserves to trans / transvestites people feelings of hatred, disgust and ridicule, dictating / preaching Christian CisHeteroNormativity and condemning those who do not follow it. Finally, threetheatrical performances / scenes are disassembled that refer to the murders of trans /transvestite people for transphobia, the feminine ideals of unreachable beauty, fragilityand fertility (prejudiced thoughts guided by religious, capitalist and patriarchal concepts) and disgust, hate and ridicule these people for society.